The impact of local financial development and corruption control on firm efficiency in Vietnam: evidence from a geoadditive stochastic frontier analysis - Rouven E. Haschka; Helmut Herwartz; Clara Silva Coelho; Yabibal M. Walle (Journal of Productivity Analysis, 2023)
In this paper, we use a geoadditve Bayesian stochastic frontier analysis to empirically assess the impact of provincial-level financial development, corruption control, and their interaction on firm efficiency in Vietnam. Using panel data from more than 40,000 Vietnamese firms during 2006-2013, we find that financial development decreases firm efficiency, while corruption control promotes it. Moreover, financial development and corruption control interact positively in affecting firm efficiency. Our results imply that corruption control not only enhances firm efficiency directly by reducing unnecessary regulatory burdens, costs, and delays, but it also offsets potential inefficiencies that arise from increased financial development.
Keywords: C11:D22; D73; G21; O43; O47; 330; Geoadditve Bayesian stochastic frontier analysis; Financial development; Corruption control; Firm efficiency; Vietnam